Nave Bayes Classifier Method Expert System for Diagnosis of Attention Disorders and Hyperactivity in Children - Sifa Sifa; Septiaana Dewi Andriana (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2022)
ADHD, also known as Attention Deficit Disorder and Hyperactivity in Indonesian, is a psychiatric condition that makes sufferers less able to focus and more prone to excessive activity or being unable to sit still than average persons. Many people are still unaware that if a youngster exhibits excessive behavior and has poor concentration, the child may have ADHD. Even if these symptoms have manifested, many parents choose to ignore them due to the high expense and distance required to see a doctor; therefore, a professional system is required to identify the sickness. The system's creation aims to make it simpler to diagnose diseases so that they can be stopped before they start and their symptoms can be treated. The technique makes use of the MySQL database, PHP programming language, and NBC (Naive Bayes Classifier). Black box testing of a system. By showing the percentage of symptoms, Nave Bayes values, and disease solutions, the results provide an expert system for diagnosing ADHD in kids using the Naive Bayes approach.